2020
DOI: 10.3390/ijms21155239
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-Induced Upregulation of miR-711 Inhibits DNA Repair and Promotes Neurodegeneration Pathways

Abstract: Radiotherapy for brain tumors induces neuronal DNA damage and may lead to neurodegeneration and cognitive deficits. We investigated the mechanisms of radiation-induced neuronal cell death and the role of miR-711 in the regulation of these pathways. We used in vitro and in vivo models of radiation-induced neuronal cell death. We showed that X-ray exposure in primary cortical neurons induced activation of p53-mediated mechanisms including intrinsic apoptotic pathways with sequential upregulation of BH3-only mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Subsequently, the same group demonstrated that neuronal death was blocked in vitro by a pan-caspase inhibitor when cells were irradiated with moderate X-ray doses (≤32 Gray), whereas cell death was unresponsive to caspase inhibition after severe DNA damage (up to 128 Gray) and could occur by non-apoptotic (necrotic) mechanisms [ 26 ]. Very recently, similar results were obtained by another group that studied (in vitro and in vivo) the inhibition of DNA repair pathways in mouse cortical neurons following whole-body irradiation at 10 Grays [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Subsequently, the same group demonstrated that neuronal death was blocked in vitro by a pan-caspase inhibitor when cells were irradiated with moderate X-ray doses (≤32 Gray), whereas cell death was unresponsive to caspase inhibition after severe DNA damage (up to 128 Gray) and could occur by non-apoptotic (necrotic) mechanisms [ 26 ]. Very recently, similar results were obtained by another group that studied (in vitro and in vivo) the inhibition of DNA repair pathways in mouse cortical neurons following whole-body irradiation at 10 Grays [ 27 ].…”
Section: Discussionsupporting
confidence: 75%
“…Irradiation may lead to nerve cell death [ 25 , 26 , 27 ] and initiation of DNA fragmentation during apoptosis, inducing phosphorylation of H2AX [ 28 , 29 ]. Therefore, before addressing the intervention of CASP3 in the response to X-rays, we wanted to ascertain if there were measurable differences in the volumetric cellular density (measured after counting DAPI stained nuclei) among the three groups of experimental mice, i.e., if irradiation was sufficient to induce a massive cellular death within the brief temporal design of our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs have shown significant regulatory effects on cardiac hypertrophy, cardiomyocyte apoptosis, myocardial fibrosis, oxidative stress, and other pathophysiological processes in diabetic cardiomyopathy [26]. miR-711 is a versatile molecule that mediates neuronal apoptosis, neurodegenerative pathways, tumor cell behaviors, and liver injury [27][28][29][30][31][32]. Studies have also reported the role of miR-711 in regulating cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Rad54 like 2 ( Rad54l2 ), a paralog of DNA repair and recombination protein Rad54b , participated in super-helical torsion within linear DNA fragments in an ATP-dependent manner 23 . It was widely involved in replication and DNA repair 24 , previous study also reported that Rad54l2 was downregulated after radiotherapy, indicating impaired DNA repair capacity 25 . However, no systemic investigation into its role was carried out in the induction of Xp11.2 tRCC.…”
Section: Introductionmentioning
confidence: 97%